The development and assessment of behavioural markers to support counter-IED training - Nixon, Jim; Leggatt, Andrew P.; Campbell, James (Elsevier, 2014)
This article describes the method used to develop and test a checklist of behavioural markers designed to support UK military forces during Counter-Improvised Explosive Device (C-IED) training. IEDs represent a significant threat to UK and allied forces. Effective C-IED procedures and techniques are central to reducing risk to life in this safety critical role. Behavioural markers have been developed to characterise and assess non-technical skills which have been shown to be important in maintaining high performance in other safety critical domains. The aims of this study were two-fold. Firstly to develop a method which could be used to capture and assess operationally relevant behavioural markers for use in C-IED training relating primarily to non-technical skills. Secondly, to test the user acceptance of the behavioural marker checklist during military training activities. Through engagement with military subject matter experts, operationally relevant and observable behaviours seen in C-IED training have been identified and their links to stronger and weaker performance have been established. Using a card-sort technique, the content validity of each of the markers was assessed in addition to their detectability in an operational context. Following this assessment, a selection of the most operationally relevant and detectable behaviours were assimilated into a checklist and this checklist was tested in C-IED training activities. The results of the study show that the method used was effective in generating and assessing the behavioural markers using military subject matter experts. The study also broadly supports the utility and user-acceptance of the use of behavioural markers during training activities. The checklist developed using this methodology will provide those responsible for delivering instruction in C-IED techniques and procedures with a straightforward process for identifying good and poor performance with respect to non-technical skills. In addition it will provide a basis for the provision of focussed feedback to trainees during debrief.
Keywords: Behavioural marker; Non-technical skills; Improvised explosive device